2014
DOI: 10.3892/ijmm.2014.1818
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active Notch1 signaling promotes endothelial-mesenchymal transition in a conditional transgenic mouse model

Abstract: Endothelial-mesenchymal transition (EndoMT) is a process in which endothelial cells lose their cell-type-specific characteristics and gain a mesenchymal cell phenotype. The Notch signaling pathway is crucial in the regulation of EndoMT; however, its roles have not been fully studied in vivo. In a previous study, we reported the generation of transgenic mice with a floxed β-geo/stop signal between a CMV promoter and the constitutively active intracellular domain of Notch1 (IC-Notch1) linked with a human placent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…Moreover, a TEK-GFP genetic mouse model was applied for a colocalization analysis as the mesenchymal cell marker ACTA2 colocalized with TEK-GFP. The molecular mechanisms involved in the switch from an endothelial phenotype to a mesenchymal status are complicated and controlled by various signaling pathways, such as the WNT, NOTCH and TGFB pathways [53][54][55]. Consistent with a previous study [54], NOTCH1 signaling lies downstream of circHECW2-MIR30D-ATG5 as shown in our current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, a TEK-GFP genetic mouse model was applied for a colocalization analysis as the mesenchymal cell marker ACTA2 colocalized with TEK-GFP. The molecular mechanisms involved in the switch from an endothelial phenotype to a mesenchymal status are complicated and controlled by various signaling pathways, such as the WNT, NOTCH and TGFB pathways [53][54][55]. Consistent with a previous study [54], NOTCH1 signaling lies downstream of circHECW2-MIR30D-ATG5 as shown in our current study.…”
Section: Discussionsupporting
confidence: 92%
“…The molecular mechanisms involved in the switch from an endothelial phenotype to a mesenchymal status are complicated and controlled by various signaling pathways, such as the WNT, NOTCH and TGFB pathways [53][54][55]. Consistent with a previous study [54], NOTCH1 signaling lies downstream of circHECW2-MIR30D-ATG5 as shown in our current study. Given that ATG5 contains substantial numbers of acidic residues, a potential glycosylation site, protein kinase C and tyrosine kinase sites [56], further investigation was required to identify the precise mechanism that underlies the activation of the NOTCH1 pathway induced by circHECW2-MIR30D-ATG5.…”
Section: Discussionsupporting
confidence: 92%
“…no Zeg-ic-notch1/tie2-cre positive offspring were obtained, and we found that the double transgenic embryos died before e10.5 with defects in vascular development and widespread hemorrhaging. these observations were consistent with our previous studies showing the lethality of Zeg-ic-notch1/tie2-cre embryos with lack of angiogenic remodeling and branching in the yolk sacs and embryonic bodies (24,25). In these IC-Notch1 expressing embryos, the circulation system of hematopoietic cells have been developed before the death of the embryos.…”
Section: Zeg-ic-notch1supporting
confidence: 82%
“…these results contribute to the understanding of the role of notch1 signaling in leukemiagenesis/lymphomagenesis in adults. the homogenous deletion of Notch1 or constitutive activation of Notch1 under Tie2 promoter in mice all induced early embryonic lethality between 9.5-11.5 with a phenotype of disruption of vasculature (24,36). Since Notch1 and Tie2 promoter are also expressed in hematopoietic cells, defects in hematopoietic system might contribute to the phenotype.…”
Section: Ic-notch1 Expression Was Activated In Hematopoietic Cellsmentioning
confidence: 99%
“…In recent years, the Notch1 signaling pathway has attracted widespread attention (10)(11)(12)(13)(14)(15)(17)(18)(19)(20)33). However, previous studies in this field have mainly focused on the cellular (10,12,20) and animal levels (11,19,33) and no research has been carried out at the human clinical trial level. In our study, human H9c2 cells from were used to create a model of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%